EVALUATION OF ANTI-PARKINSONIAN ACTIVITY OF SEED EXTRACT OF NELUMBO NUCIFERA - M.VISHNU VARDHAN REDDY; MANMOHAN SINGHAL (International Journal of Pharma and Bio Sciences, 2014)
Methanolic seed extract of Nelumbo nucifera was partitioned with chloroform and was investigated for its antioxidant and anticataleptic effects in the haloperidol-induced catalepsy rat model by measuring various behavioral and biochemical parameters. Catalepsy was induced by administration of haloperidol (1 mg/kg, ip) in male albino rats. A significant reduction in the cataleptic scores were observed in all the drug-treated groups as compared to the haloperidol-treated group; with maximum reduction observed in the Nelumbo nucifera (200 and 400 mg/kg body weight) administered group. The biochemical parameters like thiobarbituric acid reactive substances (TBARS); catalase; and superoxide dismutase (SOD), in the brain were assessed. Haloperidol administration resulted in the increased generation of TBARS and decrease in catalase & SOD levels. The study concluded that Nelumbo nucifera treatment restored the levels of TBARS, Catalase and SOD levels in haloperidol induced catalepsy in rats.